ETIKA HUKUM DALAM POLITIK KEBANGSAAN PERSPEKTIF ISLAM: MORALITAS POLITIK PANCASILAIS - Abdul Hafid; Pikahulan, Rustam; Hasyim, Hasanuddin (DIKTUM: Jurnal Syariah dan Hukum, 2020)
The legal and political realities that have developed in Indonesia to date, there is a phenomenon that makes us all worried and uneasy. major illness experienced by our nation and country today, namely corruption and terrorism. This phenomenon is more or less closely related to what is called moral degradation in the realm of politics. moral values ​​and norms (morality) which of course in this case, have to do with political phenomena in terms of nationality, state or power. The focus of research is the existence of ethics in this case concerning human actions or behavior in terms of moral values ​​and norms (morality), which are connected with one aspect of human life, namely politics. This study aims to provide a rather enlightened generation of the nation to avoid bad deeds and to obey the applicable rules, especially in the realm of politics and understand the existence of Indonesian-style national political ethics which are considered not at all contrary to the teachings of Islam. The research method used is a qualitative method. The approach used in this study is as follows: First, the philosophical approach to values, morals or actions. Second, the interpretive approach / interpretation. Third, the juridical approach to state administration. Based on the analysis outlined in the discussion, the researcher concludes that Pancasila is a logical transcendental requirement for the implementation of all legal procedures in Indonesia which is used as a guideline for making laws and regulations, which will then be used as an instrument to assess and regulate whether a behavior or act it can be said good or bad. Likewise, the existence of Islam as a product of Allah (Almighty God) is a system of religious morality that is used by Muslims as an instrument to assess or measure whether a behavior or deed can be said to be good or bad. If the two systems of morality are linked, then it turns out that between one another (substantially or in principle) there is no trace of contradiction.